2010
DOI: 10.1007/s11703-010-1043-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect of fertilizer application on rice yield, potassium uptake in plants, and potassium balance in double rice cropping system

Abstract: A 27 years field experiment was conducted on a Fe-Accumli Stagnic Anthrosol to evaluate the effects of long-term application of fertilizer, pig manure (PM), and rice straw (RS) on rice yield, uptake, and usage efficiency of potassium, soil K pools, and the nonexchangeable K release under the double rice cropping system in South Central China. Common cropping pattern in the study was early rice-late rice-fallow (winter). The field treatments included CK (no fertilizer applied), NP, NK, NPK, and NK + PM, NP + RS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Rice cultivation receiving green manure treatments showed significantly higher uptake of K over no green manure was also reported by Pattanayak et al, (2001) Liao et al, (2010) also reported that increase in K uptake with progressive increase in the supply of NPK nutrients in rice-rice cropping system due to higher availability of these nutrients which ultimately resulted in higher biomass yield.…”
Section: K Uptake Grain and Strawsupporting
confidence: 75%
“…Rice cultivation receiving green manure treatments showed significantly higher uptake of K over no green manure was also reported by Pattanayak et al, (2001) Liao et al, (2010) also reported that increase in K uptake with progressive increase in the supply of NPK nutrients in rice-rice cropping system due to higher availability of these nutrients which ultimately resulted in higher biomass yield.…”
Section: K Uptake Grain and Strawsupporting
confidence: 75%
“…(c) In agricultural systems such as rice paddies, soil fertility decreases as the period of crop cultivation increases, implying that unfertilized rice cultivation may not be sustainable in the long run. Long-term studies show that nitrogen fertilization in rice farms significantly increases rice yields ranging from 81.9 to 92.3% (Liao et al 2010;Lu et al 2015). As a result, in a bid to maintain or increase rice yields, the application of fertilizers in rice paddies may be inevitable as a response to declining soil fertility.…”
Section: Implication Of Rice Cultivation Permanent Flooding No Fertil...mentioning
confidence: 99%
“…However, there were differences in the conclusions regarding soil fertility’s effect on N recovery efficiency (NRE). Liao et al. (2010) reported that both N fertilizer contribution rate and NRE of crops were low in soils with high fertility.…”
Section: Introductionmentioning
confidence: 99%
“…However, there were differences in the conclusions regarding soil fertility's effect on N recovery efficiency (NRE). Liao et al (2010) reported that both N fertilizer contribution rate and NRE of crops were low in soils with high fertility. On the contrary, a higher NRE was observed in high fertility soil compared to that in low fertility soil in Beatriz et al (2017).…”
Section: Introductionmentioning
confidence: 99%